A Development of Integrative Thematic Textbook with Problem-Based Learning to Improve the Critical-Thinking Ability of Elementary Students at Grade IV - Rahmawati, Fita; Muhtadi, Ali (KnE Social Sciences, 2019)
This research aimed (1) to produce an integrative thematic textbook with Problem- Based Learning that is appropriate to improve the critical-thinking ability of elementary students at grade IV and (2) to examine the effectiveness of the textbook. The design of the research was R&D by Borg and Gall. The product tests were limited test, expanded test, and operational test. The researches were conducted at SDN Semanu II, SDN Karangrejek II, and SDN Gombang II in Gunungkidul District. The subjects of the research were 110 students and 4 teachers of grade IV. The instruments of data collection were interview guidelines, observation sheets, and expert validation sheets, questionnaires of teachers’ response, students’ response scale, and test of criticalthinking ability. The effectiveness of the product was tested using quasi experiment. The data were analyzed descriptive qualitatively and quantitatively through the test of difference with significance level 0.05. The result of this research was in the form of appropriate textbook based on the assessment from media expert and material expert that categorized the textbook as “very good”. The developed product was effective to improve the students’ critical-thinking ability. The average post-test score proved it, in which experimental classes 1 and 2 gained 80.48 and 80.39. The average post-test score in control class was only 67.73. The difference of average scores was significant at calculated t score 5.579 and two-tails significance at 0.000 for the difference test between the post-test of experimental class 1 and the control class. Meanwhile, the difference of average scores was significant at calculated t score 5.845 and two-tails significance was at 0.000 for the difference test between the post-test of experimental class 2 and the control class. Keywords: Integrative thematic textbook, Problem Based Learning, critical-thinking ability